THE EFFECT OF JIGSAW II AND STUDENTS-TEACHER RELATIONSHIP ON STUDENTS’ READING COMPREHENSION - ., I GUSTI AYU WARDHANI; ., Prof. Dr. A. A. I. Ngurah Marhaeni,MA; ., Dra. Luh Putu Artini, MA., Ph.D. (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2014)
Studi eksperimen ini bertujuan untuk menginvestigasi pengaruh Jigsaw II dan hubungan siswa dan guru terhadap membaca komprehensif siswa kelas sebelas SMAN 1 Denpasar pada tahun ajaran 2013/2014. Penelitian ini menggunakan rancangan 2x2 faktorial. 92 siswa dilibatkan sebagai sampel penelitian. Mereka dipilih dengan teknik sampling acak. Data membaca komprehensif siswa dikumpulkan melalui tes pilihan ganda sedangkan data hubungan siswa dan guru dikumpulkan dengan kuesioner. Data membaca komprehensif siswa dianalisis dengan ANAVA dua jalur (Analisis Varian). Temuan penelitian ini adalah a) Jigsaw II berpengaruh secara signifikan terhadap membaca komprehensif siswa, b) terdapat interaksi yang signifikan antara metode pengajaran (Jigsaw II dan konvensional) dan tingkat hubungan siswa dan guru (tinggi dan rendah) terhadap membaca komprehensif siswa, c) bagi siswa yang memiliki hungan tinggi dengan guru, Jigsaw II berpengaruh secara signifikan terhadap membaca komprehensifnya, d) bagi siswa yang memiliki hungan rendah dengan guru, Jigsaw II tidak berpengaruh secara signifikan terhadap membaca komprehensifnya.Kata Kunci : Jigsaw II, hubungan siswa dan guru, membaca komprehensif This experimental study aimed at investigating the effect of Jigsaw II and students-teacher relationship on reading comprehension of eleventh grade students of SMAN 1 Denpasar in the academic year 2013/2014. This research applies 2x2 factorial design. 92 students were selected as sample through random sampling. Data of students? reading comprehension were collected by using multiple choice tests and the students-teacher relationship were collected by questionnaire. The data of students? reading comprehension were analyzed statistically by two-way ANOVA (Analysis of Variance) at 5% significance level. This research discovers (a) there was a significant difference in reading comprehension between the students taught by using Jigsaw and those who taught by using conventional method, (b) there was a significant interaction effect of teaching method (Jigsaw and conventional method) and students-teacher level (high and low levels) on students? reading comprehension, (c) there was a significant difference in reading comprehension between students having high relationship with their teacher taught by using Jigsaw and those taught by using conventional method, and (d) there was no significant difference in reading comprehension between students having low relationship with their teacher between the students? taught by using Jigsaw and those taught by using conventional method.keyword : Jigsaw II, student-teacher relationship, reading comprehension